Extraction chemistry of some bidentate organophosphorus compounds - Martella, L.L.; Navratil, J.D.; Santiago, W.F. (Rockwell International. Rocky Flats Plant., 1978)
The extraction chemistry of methylenediphosphonates, carbamoylphosphonates, and carbamoylmethylenephosphonates has been investigated. The bidentate organophosphorus compounds extract actinides strongly, extract lanthanides, iron, gallium, molybdenum, titanium, vanadium, and zirconium partially, and do not extract most other elements from 5 to 7 M nitric acid. The properties of the extractants and extraction mechanisms are discussed. The effect of complexing agents on the extraction of actinides and lanthanides is also presented.